Smart Ocean: A Comprehensive Review of Artificial Intelligence-Driven Ocean Monitoring, Forecasting, Exploration and Conservation - Islam, Md Ariful; Sadi, Sadia Haque; Shampa, Mosa Tania Alim (BIMRAD Journal, 2026)
Tackling the unprecedented challenges faced by oceans due to pollution, climate change, and over-exploitation requires sustainable solutions for monitoring, predicting, and conserving marine resources. The emergence of artificial intelligence (AI) plays a pivotal role in advancing marine science and research, enabling efficient extraction of valuable information to aid in policy formulation. This systematic review assesses the role of AI transformation to address the crucial challenges arised in ocean resource exploration, conservation and monitoring. This review identifies four shortcomings in real-world implementation such as biases of geographical data, over-reliance on synthetic datasets, computational constraints, gaps in model interpretability. To address the geographic biases, it is required to have benchmark datasets on diverse marine ecosystems. The integration of AI development reveals that illegal fishing detection can be detected successfully with 99% precision, the coral reef can be mapped with 80% accuracy, the ship fuel can be saved about 6.64% with optimization using reinforcement learning (RL). This review thoroughly highlights AI-based technology methodologies relevant to selecting suitable techniques for specific applications in marine resource management. By analyzing past studies, this work identifies research gaps to explore in future studies, including availability of data, model interpretability, ethical risks, and cost effectiveness. A three-tiered action framework has been proposed in this review: international data-sharing protocol establishment, marine AI system standard certification and multidisciplinary innovations hub creation to mitigate the gap between conventional and AI approach. BIMRAD Journal VOLUME 6, ISSUE 1, DEC 2025; PP-83-122